2007
DOI: 10.3892/or.18.5.1321
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib and bicalutamide show synergistic effects in primary cultures of prostate cancer derived from androgen-dependent naive patients

Abstract: Abstract. We previously demonstrated that the inhibition of the epidermal growth factor receptor (EGFR) signalling affects the endocrine therapy responses of prostate cancer (PCa) cells and that bicalutamide (BCLT) is able to reinforce PI3K activity through mechanisms involving PTEN decrement and EGFR and Her2 activities. The aim of this study was to evaluate if the hormonal therapy with BCLT can affect the EGFR-targeted therapy using primary cultures obtained from 22 human PCa tissues harvested after radical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…One study found that gefitinib and bicalutamide showed synergistic effects in primary cultures of prostate cancer derived from androgen-dependent naive patients [ 53 ]. Another study discovered that gefitinib-trastuzumab combination showed promising clinical activity in hormone refractory prostate cancer [ 54 ].…”
Section: Case Studiesmentioning
confidence: 99%
“…One study found that gefitinib and bicalutamide showed synergistic effects in primary cultures of prostate cancer derived from androgen-dependent naive patients [ 53 ]. Another study discovered that gefitinib-trastuzumab combination showed promising clinical activity in hormone refractory prostate cancer [ 54 ].…”
Section: Case Studiesmentioning
confidence: 99%
“…For example, in MDA PCa 2a prostate cancer cells, the AR antagonist hydroxyflutamide proved more efficacious when combined with cetuximab and trastuzumab [126]. Significantly, in androgen-dependent PCa cell lines, co-administration of gefitinib and bicalutamide resulted in concurrent inhibition of AR and ErbB1/ErbB2 pathways, causing a significant delay in the onset of ErbB-driven castration resistance [127]. The same principle has been suggested for PCa patients who have undergone radical prostatectomy and radiation therapy - lapatinib plus an anti-androgen appear to offer a better therapeutic option than lapatinib alone 2 .…”
Section: Erbb3 and Tki Resistancementioning
confidence: 99%
“…The concomitant increament in the EGFR and Her2 expression synergizes with the reduction of PTEN in the upmodulation of Akt activity. Further we have previously demonstrated that the EGFR inhibitor, gefitinib, is able to synergize with BCLT in AR-positive cell lines in vitro (35,36) and that effectiveness of this treatment regimens was modulated by PTEN/Akt activity. In addition we have also demonstrated that inhibition of PI3K-dependent signaling alone induces proliferative arrest (26).…”
Section: Discussionmentioning
confidence: 96%